2012
DOI: 10.1038/ajg.2011.484
|View full text |Cite
|
Sign up to set email alerts
|

Lower Serum IL-10 Is an Independent Predictor of IBS Among Volunteers in Mexico

Abstract: The lower serum IL-10 in our subjects fulfilling IBS Rome II symptom criteria suggests an altered immune regulation. Further studies are needed to elucidate if a lower serum IL-10 may be useful as a biomarker for IBS in the Mexican population, especially for women with IBS-D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 35 publications
2
47
0
7
Order By: Relevance
“…However, a convincing history of enteritis with onset of IBS is present only in a subset of patients with IBS (Jeffery, Quigley, Öhman, Simrén, & O'Toole, 2012). The literature reveals inconsistencies as to whether pro-and/or anti-inflammatory cytokines are altered in IBS patients (Chang et al, 2012;Schmulson et al, 2012). It is our hypothesis that in adults with IBS in whom the etiology may be due to dysbiosis, an elevation in serum anti-and pro-inflammatory cytokines may signal either a state of chronic immune stimulation and/or an alteration in cytokine signaling pathways.…”
Section: Immune Functionmentioning
confidence: 99%
“…However, a convincing history of enteritis with onset of IBS is present only in a subset of patients with IBS (Jeffery, Quigley, Öhman, Simrén, & O'Toole, 2012). The literature reveals inconsistencies as to whether pro-and/or anti-inflammatory cytokines are altered in IBS patients (Chang et al, 2012;Schmulson et al, 2012). It is our hypothesis that in adults with IBS in whom the etiology may be due to dysbiosis, an elevation in serum anti-and pro-inflammatory cytokines may signal either a state of chronic immune stimulation and/or an alteration in cytokine signaling pathways.…”
Section: Immune Functionmentioning
confidence: 99%
“…Several investigators have reported reduced levels of serum anti-inflammatory cytokine IL-10 12,13 or no difference between those with IBS and controls. 14 The aim of the current study is to determine whether measures such as nighttime ANS balance, lactulose/mannitol ratio (intestinal permeability measure), and serum IL-10, identified in the literature as potential markers in IBS, are predictive of outcomes with a cognitively-focused behavioral therapy.…”
mentioning
confidence: 99%
“…There is evidence of sustained inflammation in IBS supported by numerous studies that have detected low anti-inflammatory cytokines in IBS patients [35] or others that found high levels of those pro-inflammatory ones or a misbalance of the pro-and anti-inflammatory cytokine proportion [36,37]. The complex dialogue between the structures involved in maintaining the homeostasis includes interrelation of nervous, immune, and endocrine systems [30,34], where a pivotal piece is the brain that governs the humoral and neurological systems [34,38,39], in a complex network with multidirectional communicating systems [10].…”
Section: Inflammation In Ibsmentioning
confidence: 72%